2018
DOI: 10.1016/j.yebeh.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Addressing barriers to surgical evaluation for patients with epilepsy

Abstract: Although process improvement expanded the number of patients who underwent epilepsy surgical evaluation, we experienced concurrent prolongation of the time from pathway initiation to completion. Ongoing improvement cycles will focus on newly identified residual sources of bottleneck and delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In Australia, over 250,000 people, about 0.6% of all Australian's, are currently living with epilepsy, and around 3-3.5% will experience epilepsy at some point in their life [2][3][4]. Most people with diagnosed epilepsy achieve 'seizure freedom' through antiepileptic drug (AED) therapy, but approximately one-third are living with refractory epilepsy, a difficult to treat, chronic and complex condition, where seizures are not controlled effectively by an AED regime alone [5][6][7]. Epilepsy management can be further complicated by significant adverse side effects from drugs that can add to the burden of disease [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, over 250,000 people, about 0.6% of all Australian's, are currently living with epilepsy, and around 3-3.5% will experience epilepsy at some point in their life [2][3][4]. Most people with diagnosed epilepsy achieve 'seizure freedom' through antiepileptic drug (AED) therapy, but approximately one-third are living with refractory epilepsy, a difficult to treat, chronic and complex condition, where seizures are not controlled effectively by an AED regime alone [5][6][7]. Epilepsy management can be further complicated by significant adverse side effects from drugs that can add to the burden of disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, surgical treatment for refractory epilepsy remains underutilized internationally, and there is a disparity between the proportion of suitable candidates for surgery and those that receive surgery [11,12,15,16]. In the United States there is, on average, a 22-year delay for epilepsy related surgery after initial disease presentation, and in Australia, a 17-year delay [7,9,17,18]. There are many factors contributing to this, including the following: a tendency among neurologists to consider surgery as the 'last resort' [19:39], the inability of nonspecialist healthcare professionals (HCP) to identify refractory epilepsy, a delayed onset of refractory epilepsy from initial presentation of epilepsy was estimated as nine years [20], lack of accurate knowledge and information about other nonpharmacological treatments, such as resective surgery, poor sharing of statistical information about surgical treatment outcomes and risk, and patients' fearful attitudes toward surgery [8,9,12,17,21].…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is a global concern, with a high societal cost that is concentrated in the approximately one in three patients who have uncontrolled seizures despite adequate trials of anti-seizure medications 6–8. Access to surgical therapy, which offers up to a 50%–80% rate of freedom from disabling seizures for patients with focal-onset DRE, features particularly tight EMU bottlenecks that can result in major diagnostic and subsequent treatment delays 4 7 9 10. In one study that compared two epilepsy centres in Canada and Mexico, the average wait time from first epilepsy consult to videoelectroencephalographic (EEG) was reported as 15.1 months and 27.4 months in Canadian and Mexican centres, respectively 11.…”
Section: Ethics Challenges Unique To Epilepsy Monitoring Unitsmentioning
confidence: 99%
“…Video-electroencephalographic monitoring (VEM) is critical to the evaluation and treatment of patients with medication resistant epilepsy, defined by failure of two adequate trials of tolerated, appropriatelychosen antiseizure medications (ASM) at appropriate doses [1,2]. While some studies demonstrated that early surgical therapy for epilepsy may be more effective, the time from first seizure to VEM (TVEM) remains around 20 years and VEM remains underutilized [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For comparison, it typically takes 9 years to meet the definition of medication resistant epilepsy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature has evaluated the many factors related to the TVEM in patients with medication resistant epilepsy (see [15] for review), however there has not been a direct comparison of the factors associated with TVEM in patients with epilepsy to patients with dissociative seizures or both diagnoses. In this study, we evaluate how patient-reported clinical factors acquired during a typical neurological interview were associated with TVEM at a comprehensive epilepsy center.…”
Section: Introductionmentioning
confidence: 99%